J. Ivanauskaitės romanų "Ragana ir lietus", "Agnijos magija" veikėjų asmenybinės transformacijos - Šumauskaitė, Jurgita (Respectus Philologicus, 1999)
The writing of Jurga Ivanauskaitė has met with widely varying responses. Like the work of other postmodernists, her prose stuns not only her casual readers but the critics as well. She provides us with a new, postmodern character type - a complicated contemporary woman who struggles with spiritual contradictions and searches for answers to existential questions as she explores various cultures and undergoes a variety of religious experiences. The main theme of J. Ivanauskaitė's novels "The Witch and the Rain" and "Agnia's Magic" is the transformation of her characters. As she tells us the stories of her complex women she employs non-traditional narrative techniques and unusual points of view; beguiles us with fragments and intertextual citation; reinvigorates lexicalized meaning; experiments with the text's graphic means; and deploys the considerable force of self-reflexive narration. The best way to appreciate J. Ivanauskaitė's innovations is to let her texts speak for - disseminate - themselves.